1989
DOI: 10.1007/bf00265097
|View full text |Cite
|
Sign up to set email alerts
|

In vivo molecular sensing in diabetes mellitus: an implantable glucose sensor with direct electron transfer

Abstract: Miniature, amperometric glucose sensors were constructed for implantation in the subcutaneous tissue of normal and insulin-dependent diabetic subjects. To minimise dependence on fluctuating tissue oxygen tension, we employed the technology of mediated electron transfer, with 1,1'-dimethylferrocene acting as the redox shuttle between immobilized glucose oxidase and a platinum base electrode. In 6 normal subjects, the subcutaneous sensor responses mirrored the simultaneously-measured changes in blood glucose con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
40
0
1

Year Published

1998
1998
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(43 citation statements)
references
References 10 publications
2
40
0
1
Order By: Relevance
“…Kulcu et al (2003) replicated these Wndings in diabetic (type 1 and type 2) humans to demonstrate that as venous glucose concentrations increased, the change in interstitial glucose was less than that in venous glucose. In six normoglycemic, healthy individuals, Pickup et al (1989) reported similar changes in interstitial and venous glucose concentrations after a 75 g glucose load; however the increase in interstitial glucose concentrations lagged behind that of venous measures. Cartee et al (1989) reported during exercise, interstitial glucose concentrations in rats decreased more quickly It must be noted that in one participant, the interstitial glucose AUC was dramatically lower compared to venous AUC during the OGTT.…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…Kulcu et al (2003) replicated these Wndings in diabetic (type 1 and type 2) humans to demonstrate that as venous glucose concentrations increased, the change in interstitial glucose was less than that in venous glucose. In six normoglycemic, healthy individuals, Pickup et al (1989) reported similar changes in interstitial and venous glucose concentrations after a 75 g glucose load; however the increase in interstitial glucose concentrations lagged behind that of venous measures. Cartee et al (1989) reported during exercise, interstitial glucose concentrations in rats decreased more quickly It must be noted that in one participant, the interstitial glucose AUC was dramatically lower compared to venous AUC during the OGTT.…”
Section: Discussionmentioning
confidence: 73%
“…The venous to interstitial glucose gradient can vary from 20% (Claremont et al 1986) to 101% (Bolinder et al 1992). In addition, time delays in the rise or fall of interstitial glucose concentrations can be as much as 45 min (Pickup et al 1989;PfeiVer et al 1993). Many of these discrepancies could potentially be the result of measuring interstitial glucose during non steady-state conditions.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Blood glucose concentrations are well correlated with subcutaneous glucose concentrations at steady-state (1)(2)(3)(4)(5). When the blood glucose concentration increases rapidly (3,4,(6)(7)(8)(9) or decreases (7,9,10) there is, however, a time lag, resulting in a transient difference between the blood and subcutaneous glucose concentrations. With recently developed 5 ϫ 10 Ϫ4 cm 2 active area, Ͻ150-sec response time flexible glucose electrodes, small enough to be implanted not only subcutaneously but also in the jugular vein of rats, it became possible to continuously and simultaneously track the two concentrations and to better time resolve them (11,12).…”
mentioning
confidence: 99%
“…In conclusion, the major drawback of subcutaneously implanted electrochemical sensors is the bioinstability with unpredictable drift and reproducibility of sensor measurements. 13,20,43,45,46 The bioinstability is partly explained by the sensor design, but obviously is also affected by the subcutaneous inflammatory reaction to implanted sensors. Suggested causes of the observed bioinstability have been attributed to protein/cellular biofouling in or on the membrane, tissue interferents affecting the electrode, enzymatic dysfunction, or unstable levels of oxygen.…”
Section: Mg/dl Smbg Cgmmentioning
confidence: 99%